Determinants of COVID-19 vaccine acceptance in Mozambique: The role of institutional trust. Issue 17 (24th April 2023) - Hu, Bo; Yang, Wei; Bouanchaud, Paul; Chongo, Yolanda; Wheeler, Jennifer; Chicumbe, Sergio; Chissano, Marcos
Highlights: COVID-19 vaccine acceptance in Mozambique changed considerably even over quite short time periods. A higher level of trust in institutions was associated with higher levels of COVID-19 vaccine acceptance, and this association was stronger among younger people. The overall decrease in vaccine acceptance over time was mainly driven by people with a lower level of institutional trust. Abstract: Background: Vaccination plays an imperative role in protecting public health and preventing avoidable mortality. Yet, the reasons for vaccine hesitancy in African countries are not well understood. This study investigates the factors associated with the acceptance of COVID-19 vaccine in Mozambique, with a focus on the role of institutional trust. Methods: The data came from the three waves of the COVID-19 Knowledge, Attitudes and Practices (KAP) survey which followed a cohort of 1, 371 adults in Mozambique over six months (N = 3809). We examined vaccine acceptance based on three measurements: willingness to take vaccine, perceived vaccine efficacy, and perceived vaccine safety. We conducted multilevel regression analysis to investigate the trajectories of, and the association between institutional trust and vaccine acceptance. Results: One third of the survey participants (37%) would definitely take the vaccine. Meanwhile, 31% believed the vaccine would prevent the COVID-19 infection, and 27% believed the vaccine would be safe. There was a significant decrease in COVID-19 vaccine acceptance between waves 1 and 3 of the survey. Institutional trust was consistently and strongly correlated with different measures of vaccine acceptance. There was a greater decline in vaccine acceptance in people with lower institutional trust. The positive correlation between institutional trust and vaccine acceptance was stronger in younger than older adults. Vaccine acceptance also varied by gender and marital status. Conclusions: Vaccine acceptance can be volatile even over short periods of time. Institutional trust is a central driver of vaccine acceptance and contributes to the resilience of the health system. Our study highlights the importance of health communication and building a trustful relationship between the general public and the institutions in the context of a global pandemic.